Penerapan Ranah Digital Marketing Funnel Untuk Meningkatkan Strategi Penjualan Graha Office Dengan Analisis SWOT - Rafidah Amelia Anastasya; Yekti Condro Winursito (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Current business developments have moved from conventional systems to digital marketing systems and the use of digital marketing is the right opportunity for current developments in Indonesia. However, in its current condition, there are still business actors who do not understand digital marketing and lack awareness among the public or entrepreneurs to utilize digital media as a means to develop their activities. In the research, the researcher used a data processing method with a digital marketing funnel and the data was processed using SWOT analysis. Based on these problems, digital marketing training was carried out. This research aims to find out research results that can increase understanding of digital marketing funnel sales at Graha Office. It is hoped that the findings of this research can help companies formulate more effective digital marketing strategies that focus on achievement.